A Study on Diglossia Used by Helen Keller as The Main Character in George Sullivan's Novel "Helen Keller" - Azizah, Nur; Sudiran, Sudiran (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2015)
A Study on Diglossia Used by Helen Keller as The Main Character in George Sullivan's Novel "Helen Keller"